Applications of the Method of Direct Communication to Few Selected Social Problems: Evaluating the Impact of Direct Communication on Social Problems (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The cases chose for study are such where the 'direct communication is fundamental or where this technique supplements the other strategy for communication like mass communication or' gathering communication. We will manage the cases individually and attempt to assess the job of 'direct communication' technique refrains other communication methodologies like gathering to bunch or over all mass communication. There is no direct method of getting quantitative gauges however subjective judgment should effectively establish 'direct communication' procedure to the problems viable just as to the problems of comparable nature. We will organize the problems, where the job of 'direct communication procedure' is in a plunging request, with the first having greatest job.